Pantun as the Context of Da'wah in Islam - Meylani, Auliya; Faridah, Faridah; Hasibuan, Nisa Hafzhiyah; Panjaitan, Devi Hertina; Serungke, Mayang; Rambe, Nursamsia (Program Pascasarjana UIN Sumatera Utara, 2024)
Pantun is a form of Malay poetry used to express complex ideas and emotions. Pantun has appeared in this area for at least 500 years. Pantun has a clear a-ba-b rhyme scheme. Pantun can be channeled in the form of music, songs and writing. The aim of this research is to look at the delivery of da'wah using pantun media and the meaning contained therein. This research is a type of qualitative descriptive research that focuses analysis on content. This research uses reading and note-taking techniques as the data to be found is based on the research object. The data obtained is in the form of Islamic education in Pantun Melayu. The results of the research can be seen from the use of pantun as a medium for da'wah, the content of the pantun is one theme in al-Azhar's interpretation of 'the beauty of the sea' (wa ayatun lahum anna hammalna dzurriyatahum fi al-fulq al-masyhun). Hamka explained the beauty of the ark in rhyme verses. Anak tiung on rambutan, singing with a beak, stunned the ship in the sea, came the wind sailing far away. Ships that sail in the middle of the ocean are proof of the greatness and power of Allah SWT, which can transport people and their necessary goods from one place to another. From this pantun, according to Hamka, the message of da'wah that can be taken is the advice to see the greatness, breadth and depth of the ocean as Almighty, Most Vast and Most Glorious, Allah SWT. The vast oceans seen by the eye are actually very small compared to the vastness of space. provisions, Bring two or three strings, If it's an inch long, Don't let the sea be guessed. Apart from that, da'wah that includes rhymes will have a new atmosphere, namely a relaxed, comfortable atmosphere, not tense, not monotonous and boring. The congregation will receive the da'wah message with a feeling of comfort. This will certainly strengthen da'wah activities in the general public.